Sensitive mutation detection in heterogeneous cancer specimens by massively parallel picoliter reactor sequencing - Thomas, Roman K; Nickerson, Elizabeth; Simons, Jan F; Jänne, Pasi A; Tengs, Torstein; Yuza, Yuki; Garraway, Levi A; LaFramboise, Thomas; Lee, Jeffrey C; Shah, Kinjal; O'Neill, Keith; Sasaki, Hidefumi; et al. (Nature medicine, 2006)
The sensitivity of conventional DNA sequencing in tumor biopsies is limited by stromal contamination and by genetic heterogeneity within the cancer. Here, we show that microreactor-based pyrosequencing can detect rare cancer-associated sequence variations by independent and parallel sampling of multiple representatives of a given DNA fragment. This technology can thereby facilitate accurate molecular diagnosis of heterogeneous cancer specimens and enable patient selection for targeted cancer therapies. NOTE: In the version of this article initially published, it should have been acknowledged that Jan F. Simons, in addition to Roman K. Thomas and Elizabeth Nickerson, contributed equally to this work. The error has been corrected in the HTML and PDF versions of the article.